Seismic performance assessment of knee bracing equipped with shape memory alloys - Mussa Mahmoudi (Iranian Society of Structrual Engineering (ISSE), 2016)
According to current seismic design codes, the serviceability of the building is not necessary after the sever earthquakes but the life safety is important. It is caused to reduce the cost of construction. In recent years, the researchers have proposed the new methods and materials to improve the purposes of seismic design and to reduce the cost of construction. For example, the use of materials such as shape memory alloys (SMA) with high elastic property and low residual strain was suggested. In this study the use of these alloys is evaluated for steel knee bracing. The result showed that the structures with SMA remain survival during the sever earthquakes with low retrofitting.